2017
DOI: 10.1088/1674-1056/26/12/126203
|View full text |Cite
|
Sign up to set email alerts
|

Variations in defect substructure and fracture surface of commercially pure aluminum under creep in weak magnetic field

Abstract: Commercially pure polycrystalline aluminum of grade A85, as a test material, is investigated. Using scanning and transmission electron microscopy the aluminum fine structure and fracture surface are analyzed. Fractures are studied in the regime of creep with and without a simultaneous effect of 0.3-T magnetic field. It is found that the application of a magnetic field in a linear stage of creep leads to substructure imperfection increasing. Furthermore, the magnetic field effect on aluminum in the process of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The aluminum alloy's applications in a preloaded environment demand for a more detailed investigation to its thermomechanical behavior for determining the safety of materials, designing components, and service performance assessment. [6] High energy, continuous wave lasers are a proficient source of varying levels of machining or damaging to structural materials. Studies about the laser damage effect of aluminum, focusing on continuous laser [7][8][9][10] as well as high pulse laser, [11][12][13][14][15] were carried out frequently during the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum alloy's applications in a preloaded environment demand for a more detailed investigation to its thermomechanical behavior for determining the safety of materials, designing components, and service performance assessment. [6] High energy, continuous wave lasers are a proficient source of varying levels of machining or damaging to structural materials. Studies about the laser damage effect of aluminum, focusing on continuous laser [7][8][9][10] as well as high pulse laser, [11][12][13][14][15] were carried out frequently during the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…17 Gromov et al studied the evolution of defect substructure, fracture surface and dislocation substructure of aluminum creep under the action of the weak electric potential. 18,19 Conrad et al proposed that the high mobility of dislocations due to the electric current played an important role in such effects via the studies on the influence of electropulsing to the recrystallisation of metallic material. 13,[20][21][22][23] A number of researches on the applications of electropulsing, electric field and electromagnetic field in rolling and drawing process for metal materials have been reported, while the studies on using them in turning process can rarely be found to date.…”
Section: Introductionmentioning
confidence: 99%
“…17 Gromov et al studied the evolution of defect substructure, fracture surface and dislocation substructure of aluminum creep under the action of the weak electric potential. 18,19 Conrad et al proposed that the high mobility of dislocations due to the electric current played an important role in such effects via the studies on the influence of electropulsing to the recrystallisation of metallic material. 13,2023…”
Section: Introductionmentioning
confidence: 99%